A Numerical Study on the Ion Production in the INTI International University Plasma Focus Machine using Nitrogen Gas - Arwinder, Singh; Teh, Thiam Oun; Ng, Xue Yinn; Ng, Chee An; Wong, Jun Wen; Saw, Sor Heoh; Lee, Sing (2018)
In this paper, a numerical study on the production of ions beam and its energy in nitrogen gas using the Lee model code was carried out using the INTI International University plasma focus machine experimental current waveform results of 480 shots (120 shots at each pressure). It has been found that if the INTI International University plasma focus machine is to be used for material hardening the best results, from the viewpoint of ion beam energy will be obtained at 1 Torr